The minimally invasive surgical local osteo-enhancement procedure (LOEP) to deliver a resorbable, tri-phasic calcium-based implant material to address bone loss and strengthen the proximal femur - Goost, H.; De Schepper, J.; Rölfing, J. D.; Aguado, H.; Howe, J.; Huber, B. (Frontiers in Surgery, 2025)
With global population growth and advancing age, fragility fractures present a major healthcare challenge that current approaches have not resolved. Although pharmacological agents have been shown to reduce fragility fracture risk, there remain unmet needs in clinical care, especially for patients at imminent risk of hip fracture, given the delay between treatment initiation and observed protective effect. This gap suggests a need for novel approaches, including hip procedures that strengthen bone locally and quickly. The purpose of this report is to describe a procedural technique that has been shown in ex vivo and clinical studies to rapidly enhance proximal femur biomechanical properties and leads to new bone formation. Local osteo-enhancement procedure (LOEP) is a minimally invasive surgical procedure to address bone voids in the pelvis and extremities, including in the proximal femur, due to trauma and disease such as osteoporosis. After surgical preparation of voids within the femoral neck and intertrochanteric regions of the proximal femur, a resorbable, triphasic, calcium-based implant material, AGN1, is delivered to that site. Clinical studies demonstrate consistent implant material resorption, concurrent replacement of the material with bone, and a significant, durable increase in areal bone mineral density (aBMD). The procedural technique has been studied as a standalone procedure and as concomitant surgery taking place in the same operative session as the surgical treatment of a contralateral index hip fragility fracture. In the study of concomitant use, LOEP was reported not to disrupt the standard of care for mobilization and rehabilitation for hip fracture. The clinical studies completed suggest that the procedure demonstrates an acceptable safety profile and has the potential to reduce the incidence of hip fragility fractures.